An Exercise Counseling Intervention in Minority Adults With Heart Failure. Issue 3 (May 2017) - McCarthy, Margaret M.; Dickson, Victoria Vaughan; Katz, Stuart D.; Chyun, Deborah A.
Abstract: Purpose: The primary aim of this study was to assess the feasibility of an exercise counseling intervention for adults of diverse race/ethnicity with heart failure (HF) and to assess its potential for improving overall physical activity, functional capacity, and HF self-care. Design: This study was a quasi-experimental, prospective, longitudinal cohort design. Methods: Twenty adults were enrolled and completed the 6-minute walk and standardized instruments, followed by exercise counseling using motivational interviewing. Each received an accelerometer, hand weights, and a diary to record self-care behaviors. Participants were followed via phone for 12 weeks to collect step-counts, review symptoms, and plan the following week's step goal. Findings: Results indicate that this intervention was feasible for most participants and resulted in improvements in physical activity, functional capacity, and self-care behaviors. Conclusion/Clinical Relevance: Brief exercise counseling may be an appropriate option to improve outcomes for stable patients with HF and may be tailored to fit different settings.